2018
DOI: 10.1111/joa.12877
|View full text |Cite
|
Sign up to set email alerts
|

The digital human forearm and hand

Abstract: How changes in anatomy affect joint biomechanics can be studied using musculoskeletal modelling, making it a valuable tool to explore joint function in healthy and pathological joints. However, gathering the anatomical, geometrical and physiological data necessary to create a model can be challenging. Very few integrated datasets exist and even less raw data is openly available to create new models. Therefore, the goal of the present study is to create an integrated digital forearm and make the raw data availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Lieber(1990-92) [46,47] correspond to mean ± 1 standard deviation from 5 to 8 specimens whereas Mirakhorlo(2016) [20], Goislard(2018) [19] and Kerkhof(2018): [21] reported data for a single specimen. The optimal fibre length in the current study was estimated by multiplying the optimal belly length Lieber(1990-92) [46,47] correspond to mean ± 1 standard deviation from 5 to 8 specimens whereas Mirakhorlo(2016) [20], Goislard(2018) [19] and Kerkhof(2018): [21] reported data for a single specimen. The optimal fibre length in the current study was estimated by multiplying the optimal belly length ( opt L ) by the index of architecture at maximal activation ( opt a i ) [45].…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lieber(1990-92) [46,47] correspond to mean ± 1 standard deviation from 5 to 8 specimens whereas Mirakhorlo(2016) [20], Goislard(2018) [19] and Kerkhof(2018): [21] reported data for a single specimen. The optimal fibre length in the current study was estimated by multiplying the optimal belly length Lieber(1990-92) [46,47] correspond to mean ± 1 standard deviation from 5 to 8 specimens whereas Mirakhorlo(2016) [20], Goislard(2018) [19] and Kerkhof(2018): [21] reported data for a single specimen. The optimal fibre length in the current study was estimated by multiplying the optimal belly length ( opt L ) by the index of architecture at maximal activation ( opt a i ) [45].…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
“…They found that the discrepancies between hand muscle capacities estimated from cadaver-based data, including PCSA, and from dynamometry were higher for wrist extensors, including ECRB and ECRL, than for finger extensors, including EDC. However, the fact that the EDC maximal isometric force estimated based on effective strength measurements was lower than when using cadaver PCSA of[19] and[21] was surprising. The results from Goislard de Monsabert at al.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Despite the improved SNR and the higher resolution, no morphological UHF studies have been performed in muscles, yet. Integrating 7-T images with data from computed tomography, Kerkhof et al [ 69 ] created an ex vivo complete 3D highly accurate virtual musculoskeletal model of forearm and hand, including relevant physiological parameters. This open-source study provides a free 3D anatomical model useful for further studies in physio-pathological musculoskeletal research.…”
Section: Musclesmentioning
confidence: 99%